The marriage he demands - Jackson, Brenda (Brenda Streater) (Jackson, Brenda (Brenda Streater). Westmoreland legacy: the Outlaws., 2021)
"Businessman Cash Outlaw has inherited almost all of his late mother's Wyoming ranch...but still needs the fifty acres left to her former caretaker. As negotiations with beautiful, determined Brianna Banks become much more intimate, she reveals she'll only sell him the property...if he gives her a baby! Cash's counteroffer? That the mother of his child must become his wife!"--